Mechanical and durability performance of concretes produced with steel slag aggregate and mineral admixtures. (7th February 2022) - Costa, Laís Cristina Barbosa; Nogueira, Marcela Aguiar; Andrade, Humberto Dias; Carvalho, José Maria Franco de; Elói, Fernanda Pereira da Fonseca; Brigolini, Guilherme Jorge; Peixoto, Ricardo André Fiorotti
Highlights: Concretes produced entirely with steel slag aggregates presented higher compressive strength. Incorporating 8% steel slag powder enhanced the concrete's mechanical properties. The steel slag powder presented a potential to combine free chloride similar to silica fume. The steel slag aggregate and powder reduced the chloride penetration depth of the matrix. The result of potential alkali reactivity indicated an innocuous behavior for steel slag. Abstract: The steel slag is a residue for the steel industry that is already applied in many cement-based composites, although there is a lack of studies on the durability of this material in aggressive environments. This work evaluated the durability against chloride attack of concrete produced using steel slag as aggregate and mineral admixture, called steel slag powder. For comparison purposes, reference concretes using conventional aggregates and commercial mineral admixtures (silica fume and metakaolin) were produced. The concretes produced with steel slag aggregates and steel slag powder had lower chloride penetration depths compared to conventional ones. The steel slag powder presented an ability similar to silica fume of forming Friedel salt. The concrete produced with steel slag aggregates also presented a smaller water absorption and a higher compressive/tensile strength compared to the reference one. In general, this research observed that steel slag concretes are technically feasible options for the construction sector.